Assessment of auditory dysfunction as an extra-articular manifestation in rheumatoid arthritis using brainstem auditory-evoked potential - Abeer H Ismaiel; Soha S Shaaban; Amany F Hakim; Ahmad M A. Gawad (Journal of Medicine in Scientific Research, 2021)
Objectives The paper aims to study brainstem auditory-evoked potential parameter changes in rheumatoid arthritis (RA) patients, and their relation to the duration of illness, degree of disease activity, functional stage of the disease, and intensity of pain. Materials and methods Control (group 1) comprised 25 healthy female patients of age 50–60 years, while the study group (group 2) comprised 25 female patients with RA of more than 5 years. Proven cases of RA (according to american college of rheumatology (ACR) 2010 criteria) underwent brainstem auditory-evoked potentials. The recording was carried out by using RMS EMG EPMK2. In the RA group, the following parameters were collected: number of painful and swollen joints, intensity of pain in the joints of patients evaluated by a visual analog scale (VAS) of 0–100 mm, speed sedimentation rate, a disease activity index, and functional disability of patients. Results In this study, we found in the right ear, a highly significant difference in mean peak latency of wave I between groups 1 and 2 with (P < 0.01); also, there was a significant difference in the mean peak latency of waves IV and V between groups 1 and 2 with (P < 0.05). As regards the mean interpeak latency from I to III, there were highly significant differences between groups 1 and 2 with (P < 0.01). For the left ear, there was a highly significant difference in mean peak latencies of waves I and V between groups 1 and 2 with (P < 0.01), while there was a significant difference in mean peak latency of wave II between groups 1 and 2 with (P < 0.05). The mean differences in interpeak latencies of waves I and II and III–V between groups 1 and 2 were highly significant (P < 0.00). Estimation of the correlation coefficients for the parameters of brainstem auditory-evoked potential, and the indices of disease activity, showed statistically significant correlations with the functional class and intensity of pain by the VAS. Also, there was a significant correlation between the absolute peak latency of wave I and interpeak latency of waves I–III and disease duration with P < 0.05. Conclusion The authors conclude that RA causes delayed latencies and alteration of the waves of brainstem auditory-evoked potentials due to hearing affection.